Medical simulation: Overview, and application to wound modelling and management - Dinker R. Pai; Simerjit Singh (Indian Journal of Plastic Surgery)
Simulation in medical education is progressing in leaps and bounds. The need for simulation in medical education and training is increasing because of a) overall increase in the number of medical students vis-à-vis the availability of patients; b) increasing awareness among patients of their rights and consequent increase in litigations and c) tremendous improvement in simulation technology which makes simulation more and more realistic. Simulation in wound care can be divided into use of simulation in wound modelling (to test the effect of projectiles on the body) and simulation for training in wound management. Though this science is still in its infancy, more and more researchers are now devising both low-technology and high-technology (virtual reality) simulators in this field. It is believed that simulator training will eventually translate into better wound care in real patients, though this will be the subject of further research.